Let $n\in\mathbb{N}_{>0}$, $\gamma\in\mathbb{R}_{>0}$. Let $\{a_n\}_{n}$ and $\{b_n\}_{n}$ be two sequences defined as follows $$ a_n := \sum_{k=0}^{n-1}{2k \choose k}\frac{1}{\gamma^{2k+1}} \left(1-e^{-\frac{\gamma}{n}}\sum_{h=0}^{2k} \frac{(\gamma/n)^h}{h!} \right), $$ $$ b_n := \sum_{k=0}^{n-1}{2k \choose k}\frac{1}{\gamma^{2k+1}} e^{-\frac{\gamma}{n}}\sum_{h=0}^{2k} \frac{(\gamma/n)^h}{h!}. $$ Moreover, let $$ c_n:=\left(\frac{a_n}{b_n}\right)^n. $$

My question. What can be said about the convergence of the sequence $\{c_n\}_{n}$?

N.B. This is not an homework. It is part of a problem that came up in my research some time ago. Experimentally, I observed the $\{c_n\}_{n}$ converges to a finite non-zero value for any (randomly selected) $\gamma>0$. Thus, I wonder whether there is a chance to prove this.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.